Isaiah - Watts, John D.W. (Dallas, TX Word, 1989)
Includes bibliographical references and index.
Keywords: Handel, George Frederic, -- 1685-1759; Bible O.T. Isaiah -- criticism, interpretation, etc; Bible. O.T. Isaiah -- use in Handel's Messiah